Interspecific fish hybrids in Brazil: management of genetic resources for sustainable use - Hashimoto, Diogo Teruo [UNESP]; Senhorini, Jose A.; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Wiley-Blackwell, 2012)
Serrasalmid and pimelodid fish hybrids represent important advances for aquaculture in Brazil, but they also constitute serious genetic risks to cultivated and natural populations. Serrasalmid hybrids (tambacu, tambatinga and patinga) result from crosses between Colossoma macropomum, Piaractus mesopotamicus and Piaractus brachypomus. Pimelodid hybrids (ponto e virgula, cachandia and cachapira) arise from crosses between Pseudoplatystoma corruscans, Pseudoplatystoma reticulatum, Phractocephalus hemioliopterus and Leiarius marmoratus. The problems associated with hybrids mainly result from inappropriate use because these animals are reproductively compatible with their parental species. This review shows that monitoring of fish hybrids using genetic techniques is necessary for their sustainable development in aquaculture. The genetic technologies used to identify fish hybrids include cytogenetic methods, which are considered to be low cost, and polymerase chain reaction-based molecular markers, which are associated with high throughput. Therefore, both types of genetic methodologies should be applied in monitoring programs aimed at brood stock management, wild stocks, the trade of hybrid juveniles and processed fish products in markets. Moreover, physical and genetic confinement of hybrids in aquaculture operations will be necessary to avoid the problems posed by these animals. The expected result of these measures will be the production of genetically improved animals by fish farms, allowing the sector to develop further and offering high-quality animal protein.
Keywords: fish hybrid monitoring; genetics; hybrid identification; molecular markers; sustainable aquaculture